STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DAN ETOS KERJA GURU DI SD NEGERI 05 KOTO TANGAH KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - Abu Nawas (IAIN Batusangkar, 2016)
In this qualitative study, the researcher analyzed the headmaster’s strategy on upgrading the quality of instruction and teachers’ work ethos in Primary School 05 Koto Tangah, Tanjung Emas, Tanah Datar. The results revealed that the strategies were applied by the headmaster 1) encourage teachers to be creative and innovative; 2) discipline; 3) give an advice on making lesson plan; 4) supervise the class; 5) complete the instructional infrasructure; and 6) upgrade the instructional evaluation. The strategies changed the teachers’ work ethos especially on teachers’ mindset. Keywords: Headmaster’s Strategy, Quality of Instruction, Teachers’ Work Ethos, Primary School, Tanah Datar